RELIGIOUS CURRICULUM IMPLEMENTATION: BETWEEN CHARACTER LEARNING, SPIRIT OF AND MODERNIZATION OF EDUCATION RELIGIOSITY MADRASAH IBTIDA'IYAH JAKARTA-PUSAT - evi sopandi; Achmad Siswanto (Akademika, 2019)
Character education as a national education issue is actually not new if it is associated with the long history of the founding of the Indonesian nation. This study aims to describe the implementation of religious education curriculum in Madrasah Ibtida'iyah Istiqlal, Central Jakarta in shaping the character of students. This research uses a qualitative approach with a case study method. The results of this study indicate that the character education that was initiated by MI Istiqlal Central Jakarta emphasizes intellectual, social-emotional, kinesthetic, and spiritual intelligence in children.